Two nobodies speak out : our 150 year journey and perspectives on education - Marcus, Sheldon; Vairo, Philip D. (Emerald Publishing Limited : Information Age Pub., 2011)
This book traces the journey of two individuals who have spent their lives on both sides of the teacher/professor's desk. Between them, they went from attending kindergarten to being a college president, and in that journey, they held positions ranging from classroom teacher in the New York City public schools, every rank of the professorial ladder, to almost every administrative position available in a university.In their book, Marcus and Vairo are totally candid in relating their experiences in their various roles. They are highly opinionated, but these opinions are based on the realities they encountered with students and colleagues at all levels of education.This book utilizes vignettes as well as commentaries to tell a story of two educators who have worked at every part of the United States. There is little that has happened in education since the 1940's down to the present day that is not touched on in this book. Marcus and Vairo are "insiders" with no ax to grind. They tell the truth as they see it!